Shipping conferences : a study of their origins, development, and economic practices - Deakin, B. M.; Seward, Thelma (Cambridge, England : Cambridge University Press, 1973)
This study arose from some earlier research on six sectors of public transport and communication in the United Kingdom.
Includes bibliographical references.
ne 02/03/2018
Loans
Keywords: Shipping conferences